Pemberdayaan Komunitas Pengendara di Jakarta untuk Meningkatkan Kesiapan Adopsi Mobil Listrik BYD sebagai Solusi Pengurangan Polusi Udara - Kristanto, Stevanus; Ginting S, Isnaini Hidayati; Fahrudin, Endang; Yolanda, Yolanda (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Jakarta faces a chronic air pollution crisis, with PM2.5 concentrations consistently exceeding World Health Organization (WHO) safety thresholds. The fossil fuel–based transportation sector is a major contributor to emissions, making the transition toward electric vehicles (EVs) an urgent necessity. However, community readiness to adopt electric cars remains low due to limited environmental awareness, technology-related skepticism, and insufficient understanding of charging infrastructure and government incentive schemes. This community service program aims to enhance electric vehicle adoption readiness among car users and prospective car users in Jakarta through empowerment-based interventions involving education, training, and mentoring conducted from July to October 2025. The program employed a participatory–collaborative approach with mixed-methods evaluation involving 75 participants, using pre–post questionnaires, focus group discussions, observations, and short interviews. The results indicate significant improvements across key dimensions of adoption readiness, including environmental awareness (from 2.8 to 4.1), perceptions of BYD’s technological innovation (from 3.0 to 4.2), understanding of infrastructure and incentives (from 2.5 to 3.9), and behavioral readiness to consider electric vehicles (from 28% to 67%). Qualitative findings reveal a shift from technology-related concerns toward increased confidence and practical readiness, as well as the formation of the “Emission-Conscious Driver” community as an agent of change. These findings demonstrate that a community empowerment approach is effective in strengthening societal readiness for low-emission transportation adoption and can be replicated in other urban contexts.